Pre-Professional Internships and their Relationship with Employer Satisfaction of Accounting Students at a Technological Institute - Sánchez Córdova, Edgar Daniel (2022)
Given the demands of the globalized and competitive job market, higher technical institutes must improve the training of technical professionals, especially in recent years when the COVID-19 pandemic has caused unemployment and underemployment. Pre-professional internship constitutes one of the fundamental components of quality technical education. In this study, the relationship between the performance in pre-professional internships, rated by the Instituto de Educación Superior Tecnológico Público Aenor Orrego, and the satisfaction of the expectations of the employer was studied in order to find the degree of congruence between the training entity and the requirements of the employers. The research is of a descriptive correlational type, since it considers the analysis of paired samples, without manipulating the variables. The results show a good, direct and positive correlation. The educational impact on employability would be notable if we consider the needs of employers; it would also contribute to the economic growth and welfare of the country.